Matrix stiffness influences drug resistance to gemcitabine analog and AZD 1775 combination in PDAC organoids - Jonathan Barajas; Zhi Yang; Edward Agyare; Xueyou Zhu; Saun-Joo Yoon; Bo Han (PLoS ONE, 2025)
Background Pancreatic ductal adenocarcinoma (PDAC) is among the most lethal cancers, with limited therapeutic advancements and rapid development of treatment resistance. Fatty acid-conjugated gemcitabine analogs have shown improved antitumor efficacy. This study investigates the effects of gemcitabine conjugated with caprylic acid (Gemcitabine-8C) in combination with AZD 1775, a WEE1 inhibitor, using patient-derived PDAC organoids. Methods Patient-derived PDAC cells (G43, G46) were cultured in a gelatin-based 3D organoid system with tunable stiffness to mimic the tumor microenvironment. Cells were treated with gemcitabine, Gemcitabine-8C, AZD 1775, or their combination. The study assessed treatment efficacy, extracellular matrix influence, morphology, gene expression, and drug resistance mechanisms. Results The combination of AZD 1775 and Gemcitabine-8C significantly enhanced treatment efficacy compared to monotherapies or gemcitabine with AZD 1775. G43 cells were more sensitive to treatment than G46. Increased matrix stiffness correlated with greater drug resistance. Resistant cells exhibited elevated oxidative stress, while sensitive cells showed F-actin structural alterations absent in resistant counterparts. Conclusions AZD 1775 enhances the efficacy of Gemcitabine-8C at non-toxic doses, demonstrating its potential for overcoming PDAC treatment resistance. The cell origin and tumor microenvironment plays a key role in modulating drug response, highlighting the need for microenvironment and individualized-targeted strategies.